The midwife's role in providing smoking cessation interventions for pregnant women: The views of midwives working with high risk, disadvantaged women in public sector antenatal services in South Africa. (January 2016) - Murphy, K.; Steyn, K.; Mathews, C.
Abstract: Objective: The purpose of this study was to assess the knowledge, attitudes, beliefs and current practices of South Africa midwives in relation to providing smoking cessation education or counselling to pregnant women. This was with a view to involving them in a potential smoking cessation intervention, targeting a sub-group of South African women who are at particularly high risk of the adverse pregnancy outcomes associated with smoking. Design: A cross-sectional survey of midwives, supplemented by individual, in depth, qualitative interviews. Setting: Public sector antenatal clinics serving this particular community of women in five of the major urban centres of South Africa. Participants: A total of 102 midwives were surveyed across 29 antenatal clinics and 24 were interviewed. Measurements: Self-administered survey and semi-structured, individual interviews describing constructs from the Theory of Planned Behaviour with respect to the provision of smoking cessation education/counselling, including: knowledge, attitudes, subjective norms and perceived behavioural control. Findings: The majority of midwives accepted that providing smoking cessation advice was a part of their remit, perceived prevailing social norms to be supportive and were, overall, positively predisposed to participating in a smoking cessation intervention in antenatal clinics. However, the study identified a number of constraints to midwives fulfilling this role, which affected their perceived behavioural control. These included stressful working conditions, too little time, a dearth of educational resources and a lack of knowledge of best practice intervention methods and counselling skills. Perceived patient resistance to quitting was a further obstacle. Key conclusions and implications for practice: For the intervention to be accepted and adopted by midwives, it would need to offer them an opportunity to enhance their professional knowledge and expertise, provide them with attractive educational aids and take into account the very limited time they have for smoking education. Patient-centred, best practice methods for cessation counselling may help midwives overcome the problem of patient resistance and to engage smokers in constructive discussions about smoking with a greater prospect of success.